Fractal dimension of coastline of Australia - Husain, Akhlaq; Reddy, Jaideep; Bisht, Deepika; Sajid, Mohammad (Scientific reports, 2021)
Coastlines are irregular in nature having (random) fractal geometry and are formed by various natural activities. Fractal dimension is a measure of degree of geometric irregularity present in the coastline. A novel multicore parallel processing algorithm is presented to calculate the fractal dimension of coastline of Australia. The reliability of the coastline length of Australia is addressed by recovering the power law from our computational results. For simulations, the algorithm is implemented on a parallel computer for multi-core processing using the QGIS software, R -programming language and Python codes.